Field monitoring system: Coordination and follow-up of field activities with Innovahub partners, field data registration and progress on implementation of e-Agrology - Ovando Galdámez, Jose Rausel; Jiménez, Benancio; Martínez, Oscar; García Santiago, Jorge O.; Leal Gonzalez, Abel Jaime; Borrayo, Andrea; Martínez, Jesús David; Loon, Jelle van (Bioversity International and the International Center for Tropical Agriculture, 2023)
The field monitoring activities within the partner network play a crucial role in understanding the territory, production systems, and socio-economic conditions in communities. This knowledge enables effective support for partners, facilitating better interventions. The close relationship between technicians and producers, backed by a supportive team, fosters shared interventions, considering both local knowledge and technical expertise. Identifying production issues and leveraging community experiences with crops, yields, pests, and diseases further enhances collaboration. Innovahubs' physical infrastructure includes research platforms, innovation modules, extension areas, and trial plots addressing emerging problems or expressed needs. Guatemala and Honduras recently established this infrastructure, forming the foundation for training, demonstrations, field visits, and impactful outreach to other producers. In Mexico, mature alliances have led to diverse and permanent physical infrastructure, enabling sustained impact in intervention areas. This analysis primarily focuses on the progress of physical infrastructure establishment in Guatemala and Honduras, emphasizing the initiative's current phase. In Mexico, the focus is on hubs in the southern region (Hub Pacífico Sur, Hub Chiapas, and Hub Península Yucatán), addressing similar territorial challenges to Central American interventions. While other Mexican hubs replicate lessons within their networks, local interventions vary, contributing to impacts reported separately by the end of the first cycle in 2025. With established Innovahub infrastructure in Guatemala and Honduras, the main goal is to innovate and sustainably strengthen agricultural processes. Analysis of generated information serves as a basis for future improvement processes and monitors AgriLAC's progress. Field data collection through the eagrology platform contributes to monitoring and analyzing advancements in 2023, supplying substantial datasets for future analyses. This report presents preliminary descriptive analyses of agronomic data collected in 2023 from eagrology's modules and extension areas. Maize and beans stand out as the predominant crops, mostly cultivated under rainfed systems, reflecting the initial successes of the implemented interventions.